Organisational behaviour : global and Southern African perspectives - Robbins, Stephen P., 1943-; Robbins, Stephen P; Judge, Timothy A, 1943 (Cape Town Pearson Education South Africa (Pty) Ltd, 2009)
This book is an adaptation of the US best-seller Organizational Behavior by Robbins and Judge and is based on the 13th edition. The Southern African 2nd edition includes relevant and topical research and numerous case studies and examples to illustrate theory.
What is organizational behavior -- Organisational behavior in a global and diverse context -- Foundations of individual behavior -- Attitudes and job satisfaction -- Personality and values -- Perceptions and individual decision making -- Basic motivation concepts -- Motivation: from concepts to applications -- Emotions and moods -- Foundations of group behavior -- Understanding work teams -- Communication -- Basic approaches to leadership -- Contemporary issues in leadership -- Power and politics -- Conflict and negotiation -- Foundations of organisation structure -- Organisational culture -- Human resource policies and practices -- Organisational change and stress management.
Includes bibliographical references and index.
Adults non fiction
System requirements: Microsoft Windows 2000, Windows NT4, Windows ME or Windows XP.
Keywords: Organizational behavior